2017
DOI: 10.1007/s41693-017-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobile robotic fabrication at 1:1 scale: the In situ Fabricator

Abstract: This paper presents the concept of an In situ Fabricator, a mobile robot intended for on-site manufacturing, assembly and digital fabrication. We present an overview of a prototype system, its capabilities, and highlight the importance of high-performance control, estimation and planning algorithms for achieving desired construction goals. Next, we detail on two architectural application scenarios: first, building a full-size undulating brick wall, which required a number of repositioning and autonomous locali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 22 publications
1
59
0
Order By: Relevance
“…Construction robots are classified into three types [55]: 1) teleoperated systems where robots are under human control 2) programmable construction machines, in which humans insert the specific programmed menu of function or provide the instruction of new function to robots, and 3) intelligent systems, in which fully autonomous robots accomplish required set of activities without human intervention. A plethora of research and development (R & D) in the utilisation of robotics in construction led to an extensive range of different application primarily on civil infrastructure and residential buildings, such as automation of road, concrete compaction, interior finishing and tunnel and bridge construction [2,10,22]. A few studies have been conducted to analyse productivity and cost of construction robots.…”
Section: Robotics In Constructionmentioning
confidence: 99%
“…Construction robots are classified into three types [55]: 1) teleoperated systems where robots are under human control 2) programmable construction machines, in which humans insert the specific programmed menu of function or provide the instruction of new function to robots, and 3) intelligent systems, in which fully autonomous robots accomplish required set of activities without human intervention. A plethora of research and development (R & D) in the utilisation of robotics in construction led to an extensive range of different application primarily on civil infrastructure and residential buildings, such as automation of road, concrete compaction, interior finishing and tunnel and bridge construction [2,10,22]. A few studies have been conducted to analyse productivity and cost of construction robots.…”
Section: Robotics In Constructionmentioning
confidence: 99%
“…Over time, the ability of robotic systems has grown, extending the scope of experimentation beyond the factory towards on-site applications. Examples of mobile robotic systems that can be applied for additive building manufacturing include semi-autonomous industrial robotic arms [16] and multi-agent autonomous flying robots [17], as shown in Despite the potential offered by the technology, there has been minimal research on the benefits that automation can provide to the construction sector. Initial research has explored the environmental, economic and social advantages of automation in construction, including quantification of sustainability benefits, highlighting material optimisation and functional integration [19], and the potential productivity benefits associated with the implementation of robotic systems [20].…”
Section: Automation In Constructionmentioning
confidence: 99%
“…For increased reachability, both in terms of robot reach and accessibility adjacent to obstacles such as ducting, wiring and sprinkler system, nonperpendicular approaches were utilised, greatly reducing the margin for error. Whereas robotic programming is geared in this pilot study towards sufficient for enabling variability of threshold characteristics, the current limited degrees of mobility and freedom for the robotic workspace could be improved by implementing a mobile robotic platform, and adaptive robotic programming through live-data feedback or sensorbased calibration (Doerfler et al 2016;Giftthaler et al 2017), such as continued integration of 3D photogrammetry as basis for calibration of multiple hook sequences to improve data control for robotic fabrication and overcome time constraints in the setup process.…”
Section: Adaptability and Limitations Of Adopted Robotic Protocolsmentioning
confidence: 99%